2020
DOI: 10.1111/acel.13122
|View full text |Cite
|
Sign up to set email alerts
|

The JAK1/2 inhibitor ruxolitinib delays premature aging phenotypes

Abstract: Hutchinson–Gilford progeria syndrome (HGPS) is caused by an LMNA mutation that results in the production of the abnormal progerin protein. Children with HGPS display phenotypes of premature aging and have an average lifespan of 13 years. We found earlier that the targeting of the transmembrane protein PLA2R1 overcomes senescence and improves phenotypes in a mouse model of progeria. PLA2R1 is regulating the JAK/STAT signaling, but we do not yet know whether targeting this pathway directly would influence cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 25 publications
2
32
0
1
Order By: Relevance
“…The moderate increase in life span obtained by tocilizumab administration suggests that pathogenetic pathways specifically relevant to animal survival were not rescued. For instance, despite amelioration of adipose tissue turnover and attenuation of IL6 signaling, metabolic effects related to dysregulation of other cytokines (Bidault et al, 2020; Griveau et al, 2020; Liu et al, 2019) might suddenly establish a fatal condition. Optimization of tocilizumab dosage and combination with drugs or molecular approaches already explored for HGPS treatment may pave the way to effective therapeutic strategies (Cenni et al, 2020; Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The moderate increase in life span obtained by tocilizumab administration suggests that pathogenetic pathways specifically relevant to animal survival were not rescued. For instance, despite amelioration of adipose tissue turnover and attenuation of IL6 signaling, metabolic effects related to dysregulation of other cytokines (Bidault et al, 2020; Griveau et al, 2020; Liu et al, 2019) might suddenly establish a fatal condition. Optimization of tocilizumab dosage and combination with drugs or molecular approaches already explored for HGPS treatment may pave the way to effective therapeutic strategies (Cenni et al, 2020; Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic effects linked to aberrant NF-kB signaling and interleukin 6 (IL6) increase have been observed in Lmna G609G/G609G and Zmpste24 −/− progeroid mice featuring progerin or prelamin A accumulation, while anti-inflammatory drugs have been shown to extend life span (Osorio et al, 2011(Osorio et al, , 2012. Moreover, recent studies showed that aberrant activation of JAK-STAT signaling occurs in HGPS cells and animal models and triggers SASP with increase of IL6 and IL8 (Griveau et al, 2020;Liu et al, 2019). Intriguingly, prelamin A-dependent SASP activation, including IL6 hypersecretion, has been also observed in human vascular smooth muscle cells undergoing calcification (Liu et al, 2013), a condition that is found in HGPS and contributes to disease severity (Gordon et al, 2016).…”
mentioning
confidence: 99%
“…In breast cancer, negative regulation of this gene was reported in all molecular subtypes and promoter hypermethylation of this gene has been associated with aggressive subtypes 48 . Regarding its role in chemotherapy, PLA2R1 regulates JAK/STAT signaling and the targeting of PLA2R1 overcomes senescence 49 . All those reports indicate that this gene could play an important role in the resistance and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…A number of senolytics and senomorphics have been proven to prevent or treat diverse age-related pathologies and diseases in animal models [ 1107 ]. Fisetin [ 1129 , 1138 ], the combination of dasatinib and quercetin [ 114 ], FOXO4-DRI [ 1119 ], 17-DMAG [ 1121 ], navitoclax [ 1130 ], and ruxolitinib [ 1139 ] were among the most effective compounds that reduce senescence markers in multiple tissues, restore tissue homeostasis, extend healthspan, reduce age-related pathology, and extend lifespan in progeroid or chronologically aged wild-type mice. Numerous additional anti-aging effects of senotherapeutics in human and murine cases include anti-inflammatory activity (azithromycin and ruxolitinib) [ 1115 , 1123 ], amelioration of lung fibrosis (digoxin) [ 1114 ], and promotion of hair regrowth (roxithromycin) [ 1140 ].…”
Section: Pharmacological Interventions Protecting Genomementioning
confidence: 99%